(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2015)
The article relates to the impact of seismic inertial forces on the stability of slopes. In the calculation scheme for clay soils with consistency of IL < 0.5 has been offered to take into account the seismic slope stability of inertial force, and as indicators of shear strength parameters to take the peak strength, on the basis of which to calculate the static stability. For clayey soils with consistency IL > 0.5 in the calculation scheme of stability is offered to take into account the shear strength parameters, obtained in dynamic tests, conduct static analysis excluding seismic forces.